2015
DOI: 10.4018/ijebr.2015040102
|View full text |Cite
|
Sign up to set email alerts
|

Social Media as Persuasive Technology for Business in Malaysia

Abstract: The use of social media for business purposes has been growing exponentially due to its great potential as an effective marketing tool. Nonetheless, studies which assess how effective social media can be as a persuasive technology are limited, especially in the context of developing countries. Therefore, this study attempts to evaluate the perceived impact of social media as a persuasive technology for businesses in Malaysia. To accomplish this, a questionnaire survey was conducted with 1,196 social media user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
1
15
1
2
Order By: Relevance
“…In conclusion, there is little evidence of the benefits of social media adoption on organizational performance. Despite the possible advantages of using social networks, few studies have examined this (Öztamur and Karakadılar, 2014;Vásquez and Escamilla, 2014), and most results, like ours, are inconclusive (Hassan et al, 2015;Lovejoy and Saxton, 2012).…”
Section: Practical Implicationscontrasting
confidence: 55%
See 1 more Smart Citation
“…In conclusion, there is little evidence of the benefits of social media adoption on organizational performance. Despite the possible advantages of using social networks, few studies have examined this (Öztamur and Karakadılar, 2014;Vásquez and Escamilla, 2014), and most results, like ours, are inconclusive (Hassan et al, 2015;Lovejoy and Saxton, 2012).…”
Section: Practical Implicationscontrasting
confidence: 55%
“…Both Wong (2012) and Kwok and Yu (2013) found that Facebook adoption had a positive effect on SMEs' sales performance. Hassan et al (2015) noted that social media can have a significant impact on business by significantly influence purchasing decisions. These studies are consistent with previous technology adoption literature that found that technology adoption had a positive impact on both financial and non-financial performance (Damanpour et al, 1989;Scupola and Nicolajsen, 2013;Thong, 2001;Tushman and Nadler, 1986;Zhu et al, 2003).…”
Section: Impact Of Social Media On Business Performancementioning
confidence: 99%
“…To this inference, the Wong (2012) and Kwok and Yu (2013) studies have shown that the implementation of Facebook has had a significant positive influence on market growth of SMEs. In addition, Hassan et al (2015) argued that social media may have a substantial effect on the buying decisions of potential customers. The findings of Rodriguez et al (2015) underscored previous studies by arguing that the use of media platforms has a positive influence on customer-oriented practices which, in turn, enhance sales efficiency.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Kegiatan bisnis/perusahaan telah menyadari bahwa mereka dapat menggunakan media sosial untuk menghasilkan wawasan, merangsang permintaan, dan membuat penawaran produk yang ditargetkan melalui "penargetan perilaku". Pada beberapa penelitian tentang pengaruh media sosial terhadap bisnis, menunjukkan bahwa media sosial terutama Facebook dan Twitter, telah digunakan secara ekstensif sebagai alat bisnis dan pemasaran di seluruh dunia, dan berdampak positif terhadap pengembangan bisnis UKM (Shahizan, 2015). Pada beberapa laporan, misalnya seperti yang dilakukan oleh Socialbakers menunjukkan bahwa sebagian besar perusahaan besar telah sepenuhnya menggunakan media sosial untuk memperluas jangkauan pasar dan meningkatkan hubungan pelanggan (Socialbakers, 2021).…”
Section: Pendahuluanunclassified